Analysis of The Impact of Short Term And Long Term Liabilities on Financial Performance Before and During The Pandemic - Gunawan, Yuliana; Christy, Yunita; Suryawan, Fiona (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2024)
Amidst the uncertainty of the economic conditions caused by the covid-19, companies still require funds to finance their operational activities. Financing sourced from debt becomes an option for companies to finance their operational activities. The objective of this study is to examine the impact of short term and long term debt on financial outlook of companies economic performance before and during the pandemic in the hotel, restaurant, and tourism sub-sectors registered on the Indonesia Stock Exchange. The method used in this study is a qualitative method using secondary data available on the Indonesia stock exchange. In this study, data was analyzed using multivariate analysis. This study found a negative and significant effect of short-term liabilities on Return on Assets (ROA) with or without company size and fixed asset intensity as control variables. There was a negative and significant effect of long-term liabilities on Return on Assets (ROA) with or without company size and fixed asset intensity as control variables. Simultaneously, there is an influence of short term and long term liabilities on Return On Assets (ROA) with or without variable control. Short term and long term liabilities has a greater impact on ROA during the pandemic compared to before the pandemic.